From Horacios y Curiacios: the Allegory of Bolivar’s Death in Peru in the First Republican Decades - Barriga Calle, Irma (2021)
The political struggle took various forms during Independence, and the iconography was one of the most relevant ones. Although it was assumed that the neoclassical language should be the new language, this was not easy, and persistent colonial models remained, both by the lack of an Academy, and by its persuasive value. By analyzing Alegoría a la muerte de Bolívar (Allegory of Bolívar’s death), this article explores how this occurs in a painting made to glorify the hero and amend the unfavorable image that politicians had in Peru at the time of his death.